PERANCANGAN DAN IMPLEMENTASI KONTROLER PID ADAPTIF PADA PENGATURAN KECEPATAN MOTOR INDUKSI TIGA FASA - Halim Mudia; Rusdhiyanto Effendie; Ek Iskandar (SENTIA 2015, 2015)
Motor induction motor is most widely used in industry. The advantage of which is the construction of an induction motor is simple, the price is cheaper than other types of motor, as well as easy maintenance. Meanwhile, the lack of induction motor speed control technique is relatively difficult and requires a high starting currents around six times the nominal current of the motor. One method that was developed in the induction motor speed control is adaptive PID controller. In this final project will be designed and realized an adaptive PID controller Self Tuning Regulator (STR) to control the speed of three phase induction motor using Matlabvsoftware and ATmega16 AVR microcontroller as the input and output of the plant by communication using RS-232 serial. The purpose of this research is to try to implement adaptive PID method using Matlab as a controller.